2019
DOI: 10.1007/s10342-019-01162-w
|View full text |Cite
|
Sign up to set email alerts
|

The effect of population density on gene flow between adult trees and the seedling bank in Abies alba Mill.

Abstract: Populations of smaller effective sizes or subjected to strong environmental filtering have a higher risk of stochastic changes in their genetic properties. This study tested the hypothesis that reducing the density of parent trees combined with environmental filtering during the stage of regeneration establishment affects gene flow between the parent and offspring populations of Abies alba Mill. The genetic variation and spatial genetic structure of parent trees and seedlings were compared in the Western Carpa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…We found that silver fir was characterized by a moderate and significant FSGS at most parts of the species range (Figure 2 , Table 2 ). Among the previous studies of FSGS in silver fir, Sagnard et al ( 2011 ) and Leonarduzzi et al ( 2016 ) found a weak or absent FSGS in French and Central Italian populations, respectively, while a relatively strong FSGS was reported from populations from the Italian Alps (Mosca et al, 2018 ) and the Western Carpathians (Paluch et al, 2019 ). Based on our results together with the above mentioned studies, Sp in silver fir ranges from 0 to 0.013 with a global mean Sp of 0.005 (CI95% [–0.001, 0.01]).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…We found that silver fir was characterized by a moderate and significant FSGS at most parts of the species range (Figure 2 , Table 2 ). Among the previous studies of FSGS in silver fir, Sagnard et al ( 2011 ) and Leonarduzzi et al ( 2016 ) found a weak or absent FSGS in French and Central Italian populations, respectively, while a relatively strong FSGS was reported from populations from the Italian Alps (Mosca et al, 2018 ) and the Western Carpathians (Paluch et al, 2019 ). Based on our results together with the above mentioned studies, Sp in silver fir ranges from 0 to 0.013 with a global mean Sp of 0.005 (CI95% [–0.001, 0.01]).…”
Section: Discussionmentioning
confidence: 91%
“…The level of polymorphism in genetic markers can also vary across the species range, and influence the power of a data set for estimating kinship (Wang, 2016 ) or the spatial correlograms. The same genetic data that are used to estimate the spatial autocorrelation of allele frequencies may also be used to partially reconstruct the pedigree, which can be used to understand the mechanisms that maintain FSGS, such as the unequal reproductive success among individuals (e.g., Gerzabek et al, 2017 ; Oddou‐Muratorio et al, 2018 ; Paluch et al, 2019 ) or sex specific dispersal dynamics (Aguillon et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…We found that silver fir was characterized by a moderate and significant FSGS at most parts of the species range (Figure 2, Table 2). Among the previous studies of FSGS in silver fir, Sagnard et al (2011) and Leonarduzzi et al (2016) found a weak or absent FSGS in French and Central Italian populations, respectively, while a relatively strong FSGS was reported from populations from the Italian Alps (Mosca et al, 2018) and the Western Carpathians (Paluch et al, 2019). Based on our results together with the above mentioned studies, Sp in silver fir ranges from 0 to 0.013 with a global mean Sp of 0.005 (CI95% [-0.001, 0.01]).…”
Section: Fsgs Across the Species Range And Its Determinantsmentioning
confidence: 89%
“…The same genetic data that are used to estimate the spatial autocorrelation of allele frequencies may also be used to partially reconstruct the pedigree, which can be used to understand the mechanisms that maintain FSGS, such as the unequal reproductive success among individuals (e.g. Gerzabek et al, 2017;Oddou-Muratorio et al, 2018;Paluch et al, 2019) or sex specific dispersal dynamics (Aguillon et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Hambaeksan was not significant and the estimated Sp value (0.0036) was relatively weak compared to the average of outcrossing species (0.0126) or wind-dispersed species (0.0064) 39 . However, it was akin to Sp values of other species in Abies 40 , 41 , 42 . While there was no significant SGS in ST, BT had a stronger SGS.…”
Section: Discussionmentioning
confidence: 99%